The notorious Dr. Middleton: David Hume and the Ninewells years. Issue 2 (17th February 2023) - Stuart-Buttle, Tim
ABSTRACT: In his brief autobiography, Hume recalls how the publication of the heterodox Anglican clergyman, Conyers Middleton's Free Inquiry caused a 'furore' in England in 1748, whereas his own Philosophical Essays were 'neglected'. This has secured Middleton a very marginal place in Hume scholarship. This essay argues that Middleton's importance at a crucial stage of Hume's intellectual development, during the Ninewells years (April 1749 – July 1751), was more significant than has been allowed. On his return to Ninewells, Hume reflected on the reasons for Middleton's success. Section I considers the nature of Middleton's contributions to English philosophical-theological debate. In Section II, it is argued that this English context illuminates our understanding of both the manner and the matter of Hume's writings from the Ninewells years, which show a marked concern with the heathen philosophers' treatments of the relationship between morality and religion. Here, the similarities between Gibbon's situation in the 1760s and Hume's from the late 1740s are foregrounded: a period in which both authors confronted the challenge of translating their philosophical insights into an English 'idiom'. The essay concludes by offering some broader reflections on why intellectual historians have tended to dismiss, rather than to explore the Hume-Middleton connection.